PENERAPAN SIKLUS PDCA (PLAN-DO-CHECK-ACT) UNTUK MENGURANGI PRODUK CACAT DI PERUSAHAAN SEPATU XYZ - Burhan, Gilang Fatikhul; Gusti, Anggayuh Ridho (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The shoe industry faces many challenges in running its business, one of which is a decline in production. This is due to the continued high number of defective products produced by the existing process. This study focuses on the printing/screening division which has a high cost impact on production. This study aims to analyze the factors that cause product defects and provide suggestions for improvement efforts. The method used in this improvement is PDCA (Plan-Do-Check-Act). The PDCA approach is one method used to help improve production quality sustainably. The results of this study found that several factors causing defects were unstable/damaged heater lamp temperatures, no temperature checking standards, the use of chemicals that do not meet standards, dirty table mats and leaving residue on the glue. Based on several improvements that have been implemented, there has been a significant decrease in defective/defective product output from before. In the fourth week of April, the number of defective products was 379, a decrease compared to the previous week in the same month, which was 871 defective products.